A Method to Extract the Forensic about Negative Issues from Web. (March 2017) - Nasution, M K M; Hardi, M; Sitepu, R; Sinulingga, E
Abstract: In the social world there are many issues: positive or negative. The negative issues affect the level of social comfort. On social media such as Web, every issue positioned based on the document, which has its own attributes, such as the URL address and date of creation. Not easy to extract information from the Web, as well as to determine the origin of an issue that is flowing in the web. This paper is to derive a method for revealing the origin of an issue based on the characteristics of each webpage.